2016
DOI: 10.1007/s11270-016-3059-9
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Between Cadmium Stress and Sulphur Nutrition Level on Macronutrient Status of Sinapis alba L.

Abstract: This study evaluated the possibility of improving the macronutrient status of Cd-stressed white mustard ‘Rota’ using intensive S nutrition. Three S-SO4 (2, 6, 9 mM S) and four CdCl2 doses (0, 0.0002, 0.02, 0.04 mM Cd) in the Hoagland’s nutrient solution were conducted for 14 days. High S supply (6 or 9 mM) appears, to some extent, to affect positively the macronutrient status of Cd-stressed mustard. It increased roots and shoots contents of K and S, without significant changes in P content. Simultaneously, Mg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 34 publications
3
8
0
Order By: Relevance
“…Cd exposure-induced synthesis of GSH and PC stimulates S assimilation by Cys, a major substrate for GSH synthesis [28][29][30][31]. Recent studies reported the close relation between sulfur availability and increased plant tolerance to Cd stress [32][33][34][35][36]. S assimilation in plants starts with the uptake of sulfate by the rhizosphere via sulfate transporters (SULTR) [30,31,37].…”
Section: Introductionmentioning
confidence: 99%
“…Cd exposure-induced synthesis of GSH and PC stimulates S assimilation by Cys, a major substrate for GSH synthesis [28][29][30][31]. Recent studies reported the close relation between sulfur availability and increased plant tolerance to Cd stress [32][33][34][35][36]. S assimilation in plants starts with the uptake of sulfate by the rhizosphere via sulfate transporters (SULTR) [30,31,37].…”
Section: Introductionmentioning
confidence: 99%
“…Plants exposed to Cd usually exhibit lowest nutrient contents because Cd decreases plant biomass production, while nutrient content is positively correlated to biomass production (EKVALL; GREGER, 2003;CLEMENS, 2006;MATRASZEK et al, 2016aMATRASZEK et al, , 2016b.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in S concentration is a result of highest S supply (DAVIDIAN; KOPRIVA, 2010). It should be remembered that S well-nourished plants are more tolerant to Cd, which is essential for Cd phytoextraction DEDE;OZDEMIR, 2016;MATRASZEK et al, 2016aMATRASZEK et al, , 2017RABÊLO;AZEVEDO;. Sulfur can reduce Fe oxidation in the roots of plants exposed to Cd, which decreases Fe plaques stability (GAO et al, 2010), and possibly favors Mn 2+ uptake, which is essential to decrease the oxidative stress induced by Cd, since Mn acts on ROS detoxification in mitochondria and peroxisomes (Mn-SOD) (GILL; TUTEJA, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations